1990
DOI: 10.1089/gyn.1990.6.71
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Management of Adnexal Cystic Masses

Abstract: Four hundred twenty of 481 patients with adnexal cystic masses (508 cysts) confirmed by laparoscopy were treated by translaparoscopic surgery only. The remaining 61 patients were treated by laparotomy for one of the following reasons: malignancy or suspicion of malignancy (19 cases) and dense adhesions or large cysts (42 cases).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0
3

Year Published

1992
1992
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(33 citation statements)
references
References 17 publications
1
29
0
3
Order By: Relevance
“…More than half of the patients having an adnexectomy were postmenopausal. In the recent literature, the rate of conservative laparoscopic treatment varies from 35 to 93 % [1,4,7,18,20].…”
Section: Discussionmentioning
confidence: 99%
“…More than half of the patients having an adnexectomy were postmenopausal. In the recent literature, the rate of conservative laparoscopic treatment varies from 35 to 93 % [1,4,7,18,20].…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian torsion has been found to represent between 2.5-7.4% of all cases of acute abdomen (Anteby et al 1975;Hibbard 1985). Thus, it is not uncommon for the diagnosis to be made only after emergent diagnostic laparoscopy (Mage et al 1989;Porpora and Gomel 1997). Some reports have observed that elevated levels of D-dimer, IL-6, and TNF in preoperative blood work may accompany torsion of ovarian tumor, but to date no specific marker has been established (Descargues et al 2001;Chiou et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In the treatment of torsion of ovarian tumor, some studies have recommended diagnostic laparoscopy as a first phase, to release the torsion, followed by a definitive surgery for the ovarian tumor as the second phase (Mage et al 1989;Reich et al 1992;Porpora and Gomel 1997;Argenta et al 2000). Torsion of an ovarian tumor is an emergency that often requires surgery without extensive preoperative evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ovarian torsion has been found to represent between 2.5% and 7.4% of surgical cases of acute abdomen [7,8]. Thus, it is not uncommon for the diagnosis to be made only after emergency diagnostic laparoscopy [9,10]. Currently, there is no specific blood biomarker for tumor-related ovarian torsion [11,12].…”
Section: Discussionmentioning
confidence: 99%